Plant Natural Products: Promising Resources for Cancer Chemoprevention - Li Ma; Mengmeng Zhang; Rong Zhao; Dan Wang; Yuerong Ma; Li Ai (Molecules, 2021)
Cancer is a major factor threatening human health and life safety, and there is a lack of safe and effective therapeutic drugs. Intervention and prevention in premalignant process are effective ways to reverse carcinogenesis and prevent cancer from occurring. Plant natural products are rich in sources and are a promising source for cancer chemoprevention. This article reviews the chemopreventive effects of natural products, especially focused on polyphenols, flavonoids, monoterpene and triterpenoids, sulfur compounds, and cellulose. Meanwhile, the main mechanisms include induction of apoptosis, antiproliferation and inhibition of metastasis are briefly summarized. In conclusion, this article provides evidence for natural products remaining a prominent source of cancer chemoprevention.